Preliminary study on the anti-inflammatory and antioxidant activities of the leave extract of Hyptis fruticosa Salzm. ex Benth., Lamiaceae - Andrade,Alexandre M. (2010)
Various species of Hyptis are used in folk medicine as anti-inflammatory. In order to evaluate the actions of Hyptis fruticosa Salzm. ex Benth., Lamiaceae, studies were performed on anti-inflammatory and antioxidant activities. The ethanol extract (EE) of H. fruticosa leaves and its n-CH, CHCl, EtOAc, and MeOH/HO partitions were used in the following experiments. Oral treatment with the EE of H. fruticosa leaves (100, 200, and 400 mg/kg) or its n-C6H14, EtOAc, and MeOH/H2O partitions (50, 100, and 200 mg/kg) elicited inhibitory activity (p<0.05) on carrageenan-induced oedema formation and leukocyte migration into the peritoneal cavity in rats. However, the CHCl3 partition did not show any inhibitory effect on paw oedema and peritonitis experimental models. The EE and EtOAc partition present highest antioxidant potential (IC50 = 35.00±1.01 and 36.67±2.65 µg/mL DPPH, respectively), similar to the reference compound (IC50 = 16.67±1.21 µg/mL). In conclusion, H. fruticosa shows anti-inflammatory and antioxidant activities.